Influence of the stiffness-damping coupling of the foundation in the performance of a high-speed train track - Cunha, J. P. (2009)
A brief revision of previous works in the definition of deformability characteristics in soils subject to cyclic dynamic loading is presented. Based on the dependency of stiffness and damping of soils with cyclic shear strain, parametric studies were conducted to investigate the influence of the cyclic shear strain in the performance of the rail track subject to the passage of a Thalys high speed train at 314 km/h. The modeling was done through the Finite Element Method in plane strain. The results obtained in those analyses are shown and discussed. It is shown in this work the importance of the shear strain level imposed in the soil subgrade, in the response of the rail track in terms of displacements and vibrations.